Implementasi Program Dinas Sebagai Pendidikan Sinau Bareng Kota Surabaya Dalam Meningkatkan Kreativitas Belajar - Chairien Nurwulan Ghozalyfah; Susi Ratnawati; Ismail (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2024)
This study aims to evaluate the implementation of the Sinau Bareng program by the Surabaya City Education Office in improving learning creativity in the community. The research method used is qualitative with a descriptive approach, through in-depth interviews and direct observation of program participants, including students, teachers, and parents. The results of the study indicate that the Sinau Bareng program has succeeded in creating a conducive and interactive learning environment, which encourages student creativity in the learning process. This program not only helps students catch up on their academic achievements after the COVID-19 pandemic, but also provides space for students from underprivileged families to get additional tutoring. In addition, this program is effective in reactivating the function of the RW hall as a center for educational and social activities, as well as reducing students' dependence on the use of gadgets by providing alternative interesting and creative learning activities. In conclusion, the Sinau Bareng program is an effective strategy in improving learning creativity in the Surabaya community and can be used as a model for similar programs in other areas